2000
DOI: 10.1089/152460900750020900
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrician-Gynecologists' Opinions and Attitudes on the Role of Genetics in Women's Health

Abstract: Our objective was to describe gynecologists' current practice patterns and opinions on genetic screening and their perceived importance of genetic screening within individual practices. A questionnaire survey was sent to 1248 American College of Obstetrics and Gynecology (ACOG) Fellows, of whom 564 (45%) responded. Results from the 428 respondents providing genetic screening for heritable diseases or disorders are reported. Forty-four percent of respondents believe advances in the treatment of genetic diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 3 publications
1
33
1
Order By: Relevance
“…This can lead to uncertainty about the current state of a patient. Many doctors fail to review 21 or document family history, 22 and patients have been shown to inaccurately recall important risk factors that are used to calculate risks. 22 This type of uncertainty is common in many clinical circumstances yet is difficult to assess.…”
Section: Conceptualizing Uncertainty and Its Sourcesmentioning
confidence: 99%
“…This can lead to uncertainty about the current state of a patient. Many doctors fail to review 21 or document family history, 22 and patients have been shown to inaccurately recall important risk factors that are used to calculate risks. 22 This type of uncertainty is common in many clinical circumstances yet is difficult to assess.…”
Section: Conceptualizing Uncertainty and Its Sourcesmentioning
confidence: 99%
“…A survey of fellows of the American College of Obstetricians and Gynecologists found that 65.4% of respondents did not consider themselves well informed about genetics issues, and 86% did genetic testing without first soliciting informed consent (58). A focus group study of physicians, nurses, and counselors in the United States sought to identify the types of ethical and professional challenges that arise with genetic testing.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14] While physicians are increasingly aware of advances in genetic technology, many are not adequately trained to recognise the features of hereditary cancer predisposition that warrant referral for risk assessment, and some do not view this service as a health care priority because they are unaware of the potential benefits of genetic testing to the patient. [15][16][17][18][19][20][21] Educational resources, professional practice guidelines, and a robust literature on practical issues in cancer risk assessment are emerging, 9 22-26 but limited knowledge among primary care physicians and other healthcare providers who influence patient referrals remains a significant barrier to appropriate utilisation of cancer risk assessment services. [27][28][29][30][31] Targeted education to clinicians should facilitate the integration of genetic screening services into clinical practice, 22 32 33 but promoting cancer genetics education is a challenge, due in part to the complex health and social issues related to hereditary disease, to the rapidly evolving body of knowledge about genetic risk assessment and high risk management, and to the constraints on physician time for continued education.…”
mentioning
confidence: 99%